A construção de um dicionário histórico: o caso do Dicionário Histórico do Português do Brasil-séculos XVI, XVII e XVIII - Murakawa, Clotilde De Almeida Azevedo [UNESP] (Universidad de Santiago de Compostela, 2014)
The Historical Dictionary of Brazilian Portuguese in the 16th, 17th and 18th Centuries (CNPq) project concluded in December 2012. Containing 10,470 entries, the dictionary was built from a data bank based on documents of different types from the sixteenth to eighteenth centuries within the Brazilian colonial period. The texts chosen for the bank were produced in this period by Portuguese who came to Brazil or were already residing there. The data bank lists nearly 10 million occurrences. This article describes the theoretical and methodological procedures developed for DHPB and the approaches taken to account for linguistic facts in the data which were worth recording in a historical dictionary aiming to document the lexical repertory that gave rise to Brazilian Portuguese.
Building a historical dictionary: The historical dictionary of Brazilian Portuguese in the 16th, 17th and 18th centuries
Keywords: Brazilian colonial history; Entry; Historical context; Lexicographic definition; Lexicography; Lexicology